A new species of Caraiboscia Vandel, 1968 from South America, and a type species for Colombophiloscia gen. n. (Crustacea: Oniscidea: Crinocheta) - Leistikow, Andreas (Journal of natural history, 2001)
The South American genera Caraiboscia Vandel, 1968 and Colombophiloscia gen. n. are examined to establish their phylogenetic relationships in the light of their life histories. A new species is described in the genus Caraiboscia, whereas the latter genus replaces the name Colombophiloscia Vandel, 1968 which is an unavailable name since no type species was chosen by Vandel (1968). The taxa are described in detail and apomorphic characters supporting a sister group relationship are given. The adaptive value of these characters is discussed with respect to their life history and the probability of a convergent evolution.